Opportunities and Challenges in Artificial Intelligence (AI)-Based Islamic Religious Education Learning Evaluation - Essha Kakesha Rajabiah; Sugeng (Mazidah: Journal Of Educational Research, 2025)
This article aims to analyze the opportunities and challenges of applying AI in PAI learning evaluation, particularly in improving the objectivity, effectiveness, and personalization of the assessment process using a qualitative approach with a literature review method. This study examines various literature related to the implementation of AI in the field of education and religious learning evaluation. The results of the study show that AI has the potential to strengthen the evaluation process through assessment automation, real-time feedback, student progress analysis, and the provision of adaptive learning materials according to the needs of students. In addition, the use of Islamic chatbots has been proven to increase learning motivation and access to Islamic knowledge. However, the integration of AI in PAI evaluation also faces a number of challenges, such as the limited digital competence of teachers, data privacy issues, technological access gaps, algorithm subjectivity, and cultural and theological resistance to the use of technology in religious education. Therefore, infrastructure readiness, increased digital literacy, the development of ethical policies, and continuous training for educators are necessary to ensure that the use of AI remains in line with Islamic values and the main objectives of PAI, namely the formation of students' character and morals.